(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In the article current state reserves of Stenodus leucichtys leucichtys,Guldenstadt, 1772 in Volgensis-Caspian basin are considered. The reserves of Stenodus leucichtys